2017
DOI: 10.1088/1361-6641/aa6819
|View full text |Cite
|
Sign up to set email alerts
|

High-performance near-infrared photodetector based on nano-layered MoSe2

Abstract: In recent years, the integration of two-dimensional (2D) nanomaterials, especially transition metal chalcogendies (TMCs) and dichalcogendies (TMDCs), into electronic devices have been extensively studied owing to their exceptional physical properties such as high transparency, strong photoluminescence, and tunable bandgap depending on the number of layers. Herein, we report the optoelectronic properties of few-layered MoSe 2 -based back-gated phototransistors used for photodetection. The photoresponsivity coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 26 publications
1
49
0
Order By: Relevance
“…The photodetector utilized the plasmonic NIR resonance absorption in RWs and the high photoconductive gain from MoS 2 to achieve the detection ranging from 1000 to 1250 nm. [51] In addition to MoS 2 , many other 2D TMDs have been exploited for IR photodetection, including MoSe 2 , [52,53] MoTe 2 , [54][55][56] WSe 2 , [57,58] WTe 2 , [59] HfS 2 , [60] and PtSe 2 . [61] Ko et al have demonstrated a few-layer MoSe 2 -based NIR photodetector that possesses a high responsivity of 238 A W −1 under illumination of 785 nm, [52] several orders of magnitude higher than that of a device based on multilayer MoS 2 .…”
Section: Transition Metal Dichalcogenidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The photodetector utilized the plasmonic NIR resonance absorption in RWs and the high photoconductive gain from MoS 2 to achieve the detection ranging from 1000 to 1250 nm. [51] In addition to MoS 2 , many other 2D TMDs have been exploited for IR photodetection, including MoSe 2 , [52,53] MoTe 2 , [54][55][56] WSe 2 , [57,58] WTe 2 , [59] HfS 2 , [60] and PtSe 2 . [61] Ko et al have demonstrated a few-layer MoSe 2 -based NIR photodetector that possesses a high responsivity of 238 A W −1 under illumination of 785 nm, [52] several orders of magnitude higher than that of a device based on multilayer MoS 2 .…”
Section: Transition Metal Dichalcogenidesmentioning
confidence: 99%
“…[60] As shown in Figure 3c, the HfS 2 phototransistor exhibits an ultrahigh responsivity in excess of 3.08 × 10 5 A W −1 , ultrahigh photogain exceeding 4.72 × 10 5 , and ultrahigh detectivity over 4 × 10 12 Jones, which is superior to the vast majority of the reported 2D TMDs-based IR phototransistors. [40,52,54] Such outstanding performance might be attributed to the high crystal quality and superior field effect transistor properties of a competitive mobility of 7.6 cm 2 V −1 s −1 and an ultrahigh on/off ratio exceeding 10 8 , which minimize the defect density, the deleterious effects of defects and trap states, and facilitate photogenerated carriers transport in the HfS 2 channel. [60] More recently, the 2D noble metal dichalcogenides PtSe 2 is also emerging in IR photodetection.…”
Section: Transition Metal Dichalcogenidesmentioning
confidence: 99%
“…Due to their intriguing properties, including the ultrathin thickness, highly mechanical flexibility, suitable and tunable band gap, ultrafast optoelectronic characteristics, and easily tailored van der Waals heterostructures, 2D layered materials have been considered as the competitive IR media for next‐generation photodetectors. Special attentions have been paid to graphene, black phosphorous (BP), graphene‐based heterostructure, and transition metal dichalcogenides . However, graphene generally requires extra treatments to enhance its photon absorption because of its relatively low optical absorption coefficient .…”
Section: Introductionmentioning
confidence: 99%
“…and enhance device performance. 22,33 We discuss multilayer response of our devices towards the end of this Letter.…”
Section: Introductionmentioning
confidence: 93%